Mechanisms of the Effect of Starvation Duration on the Regulation of Feeding Rhythm and Metabolic Physiology of Cultured Large Yellow Croaker (Larimichthys crocea) - Xiaomeng Wang; Huang Liu; Chenglin Zhang; Chen Zhu; Huiyi Liu (Journal of Marine Science and Engineering)
In recent years, significant progress has been made in China in the field of deep-sea large yellow croaker (Larimichthys crocea) farming. Compared with the traditional inshore aquaculture model, deep-sea culture of large yellow croaker enjoys a wider growing space with better water quality, thus enhancing fish quality. However, deep-sea aquaculture also faces challenges such as typhoons and strong currents, which often lead to prolonged starvation in fish. Therefore, in order to further promote the technological advancement of large yellow croaker in the field of deep-sea aquaculture, this experiment aimed to investigate the effects of varying starvation durations on the feeding rhythm and physiological state of large yellow croaker. With an initial body mass of 122.62 ± 11.08 g and a body length of (17.9 ± 1.04) cm as the samples, the experiment was divided into five groups, which were starved for 0 d (S0), 2 d (S2), 4 d (S4), 8 d (S8), and 16 d (S16) before resumption of feeding. The results were as follows: under starvation stress for 8 consecutive days, the total duration of feeding gradually decreased in large yellow croaker, but increased at starvation up to 16 days. Each replicate group had 50 large yellow croakers as test subjects, for a total of 750 large yellow croakers. Analyzing the linear regression equations of S0 with S2, S4, S8, and S16 groups, it was found that the trend of rate of change in feeding duration was consistent with the total duration of feeding, i.e., it decreased during 8 days and increased at 16 days. It indicated that the rate of feeding of large yellow croaker was accelerated within 8 days of starvation, while the rate of feeding was slowed down at 16 days of starvation. Furthermore, the blood glucose concentration of large yellow croaker decreased significantly after 8 days of starvation, while it rebounded significantly in the S16 group. Meanwhile, large areas of fatty degeneration were observed in the liver on the 8th day of starvation, followed by extensive hepatocyte necrosis on the 16th day. After resumption of feeding, there was some recovery within 4 days, but hepatocytes were still extensively edematous in the S8 and S16 groups. Meanwhile, the expression of inflammatory factor genes such as IL-1β, IL-10 and TNF-α in the liver increased with the prolongation of starvation time, in which both S8 and S16 groups in the liver were significantly different from the S0 group, and after resumption of feeding, the IL-1β and TNF-α genes of the S8 and S16 groups were significantly different from those of the normal feeding group (p < 0.05), while there was no differentiation for the IL-10 gene. Therefore, based on the results of this study, it is recommended to limit the duration of starvation in the large yellow croaker to no more than 8 days.